The mammoth hunters - Auel, Jean M. (Auel, Jean M. Earth's children, 2011)
Ayla and Jondalar meet the Mamutoi, the Mammoth Hunters, and Ayla finds herself torn between the wildly jealous Jondalar and the master carver Ranec.